Innate Immune Responses Associated with Resistance against Haemonchus contortus in Morada Nova Sheep - João Henrique Barbosa Toscano; Cintia Hiromi Okino; Isabella Barbosa dos Santos; Luciana Aparecida Giraldelo; Marei Borsch von Haehling; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Journal of Immunology Research)
The immune response against Haemonchus contortus infections is primarily associated with the Th2 profile. However, the exact mechanisms associated with increased sheep resistance against this parasite remains poorly elucidated. The present study is aimed at evaluating mediators from the innate immune response in lambs of the Morada Nova Brazilian breed with contrasting H. contortus resistance phenotypes. Briefly, 287 lambs were characterized through fecal egg counts (FEC) and packed cell volume (PCV) after two independent experimental parasitic challenges with 4,000 H. contortus L3. 20 extreme resistance phenotypes (10 most resistant and 10 most susceptible) were selected, subjected to a third artificial infection with 4,000 L3, and euthanized 7 days later. Tissue samples were collected from abomasal fundic and pyloric mucosa and abomasal lymph nodes. Blood samples were collected at days 0 and 7 of the third parasitic challenge. RNA was extracted from tissue and blood samples for relative quantification of innate immune-related genes by RT-qPCR. For the abomasal fundic mucosa, increased TNFα and IL1β expression levels (P<0.05) were found in the susceptible animals, while resistant animals had IL33 superiorly expressed (P<0.05). Higher levels (P<0.05) of TLR2 and CFI were found in the abomasal pyloric mucosa of resistant animals. TNFα was at higher levels (P<0.05) in the blood of susceptible lambs, at day 0 of the third artificial infection. The exacerbated proinflammatory response observed in susceptible animals, at both local and systemic levels, may be a consequence of high H. contortus parasitism. This hypothesis is corroborated by the higher blood levels of TNFα before the onset of infection, which probably remained elevated from the previous parasitic challenges. On the other hand, resistant lambs had an enhanced response mediated by TLR recognition and complement activation. Nevertheless, this is the first study to directly associate sheep parasitic resistance with IL33, an innate trigger of the Th2-polarized response.